A case of fatal heart and liver failure accompanied by thyroid storm treated with prompt plasma exchange. Issue 3 (March 2017) - Zeng, Feibi; Takaya, Tomofumi; Yoshida, Naofumi; Ito, Tatsuro; Suto, Makiko; Hatani, Yu; Sano, Hiroyuki; Ito, Jun; Fukuoka, Hidenori; Yamashita, Tomoya; Hirata, Ken-ichi
Abstract: A 36-year-old man with a history of Graves' disease was admitted complaining of dyspnea. He was diagnosed with acute heart failure and severe liver dysfunction accompanied by thyroid storm. Left ventricular ejection fraction was 19%, and liver enzyme levels were markedly elevated followed with coagulation disorders. In addition to the conventional therapy, we performed plasma exchange emergently. Thyroid hormone levels promptly normalized, then his clinical condition improved. Finally, his cardiac and liver function almost normalized from a fatal condition without serious complications. Hyperthyroidism can cause myocardial and liver injury, hence thyroid hormone removal in acute phase is important. Prompt plasma exchange is effective in the acute phase for heart and liver failure accompanied by thyroid storm. <Learning objective: Thyroid storm is a life-threatening condition. Prompt reduction of serum free thyroid hormone is important in fatal conditions. Because plasma exchange (PE) can decrease serum thyroid hormone and improve critical condition, PE should be conducted emergently. In the present case, we promptly performed PE for the patient with potentially fatal heart and liver failure. We could treat him without any complication. We wish to emphasize the importance of prompt PE in acute phase of thyroid storm.>